2002
DOI: 10.1007/s00441-001-0479-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of TGF-β-mediated apoptosis

Abstract: Transforming growth factor-beta (TGF-beta) is a multifunctional cytokine, whose numerous cell and tissue activities include cell-cycle control, the regulation of early development, differentiation, extracellular matrix formation, hematopoesis, angiogenesis, chemotaxis, immune functions, and the induction of apoptosis. TGF-beta-mediated growth inhibition and apoptosis can be correlated with its function as a tumor suppressor. The apoptosis-inducing capacity has been investigated in many cell types. Data from ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
252
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(275 citation statements)
references
References 84 publications
13
252
0
3
Order By: Relevance
“…Although some studies indicate that TGF-β can both prevent and induce cell injury under different conditions depending on the specific paradigm (Bottner et al, 2000;, many other studies show that TGF-β is able to induce apoptosis and that Akt and downstream signaling intermediates block TGF-β induction of cell death (Samatar et al, 2002;Schuster and Krieglstein 2002). In the current study, increased glucose and TGF-β1 or TGF-β2 in combination produced greater neuronal injury in embryonic DRG than TGF-β used alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some studies indicate that TGF-β can both prevent and induce cell injury under different conditions depending on the specific paradigm (Bottner et al, 2000;, many other studies show that TGF-β is able to induce apoptosis and that Akt and downstream signaling intermediates block TGF-β induction of cell death (Samatar et al, 2002;Schuster and Krieglstein 2002). In the current study, increased glucose and TGF-β1 or TGF-β2 in combination produced greater neuronal injury in embryonic DRG than TGF-β used alone.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β comprises a family of cytokine growth factors that have several functions in the areas of cellular development, differentiation, extra cellular matrix formation and apoptosis (Lin and Moustakas 1994;Schuster and Krieglstein 2002). It has been generally accepted that functions of TGF-β family members may vary depending on cellular status and cell types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three (ER-a, ER-b and AR) of 4 steroid receptors, which we found in the current study to have higher expression after RT, were found previously to have an ability to inactivate TGF-b antiproliferative signaling pathway by inhibition of Smad3. [35][36][37][38][39] Interestingly, ER-b was the only steroid receptor to be upregulated in prostate adenocarcinoma epithelial cells after RT. We have demonstrated previously that ER-b expression is associated positively with Gleason score and primary Gleason grade with higher levels expressed in higher grade tumors.…”
Section: Discussionmentioning
confidence: 99%
“…SMAD3 plus the SMAD3-inhibitor SMAD7 were included because they are transcriptional modulators activated by TGFb1 and, in the case of SMAD7, by EGF, and because SMAD3 interacts directly with Fas. We also included CTGF, as this gene may also be involved in smad-mediated TGFb-induced cell death [18,39]. Real-time RT-PCR was performed using the ABI PRISM1 7900 HT sequence detection system with primer sets (TaqMan1 gene expression assays) supplied by Applied Biosystems (Foster City, CA).…”
Section: Methodsmentioning
confidence: 99%